Toxic shock syndrome following inguinal hernia repair: a rare condition - Yadav, Rohit Prasad; Bhattarai, BK; Gupta, RK; Shrestha, N; Ghimire, A (Journal of College of Medical Sciences-Nepal, 2014)
A 25-year-old man developed fulminant multisystem failure 28 hours after elective repair of an inguinal hernia. Toxic shock syndrome (TSS) was diagnosed. The patient recovered fully with supportive care in ICU, antibiotics, and IV human immunoglobin . To the best of our knowledge, only one case of TSS following inguinal hernia repair have ever been previously published. Journal of College of Medical Sciences-Nepal, 2013, Vol-9, No-2, 57-59 DOI: http://dx.doi.org/10.3126/jcmsn.v9i2.9689